Strategi MSDM dalam Meningkatkan Keunggulan Kompetitif: (Studi Kasus Wisata Esy yang Ada di Kecamatan Wundulako, Kabupaten Kolaka) - Lusia Erlin Rampo; Almansyah Rundu Wonua; Ismanto Ismanto (Universitas Katolik Widya Karya Malang, 2023)
This research aims to find out how HRM strategies can improve Competitive Advantage in the case study of Esy Tourism in Wundulako District, Kolaka Regency. This study uses a qualitative method. The informants in this research consisted of the owner and all employees. Esy Tourism. Data collection techniques are through observation, interviews and documentation. Meanwhile, the data analysis technique uses an interactive model, which includes data collection, data reduction, data presentation and drawing conclusions. Based on the results of research conducted by researchers, the conclusion that can be drawn is that the HRM strategy in increasing the competitive advantage of Esy tourism MSMEs still does not fully use the HRM strategy, where employee recruitment still uses a family basis and is not competent according to the HRM strategy, but other strategies already use the strategy. HRM.